2020
DOI: 10.1111/1348-0421.12775
|View full text |Cite
|
Sign up to set email alerts
|

Human immune responses elicited by an intranasal inactivated H5 influenza vaccine

Abstract: Intranasally administered influenza vaccines could be more effective than injected vaccines, because intranasal vaccination can induce virus-specific immunoglobulin A (IgA) antibodies in the upper respiratory tract, which is the initial site of infection. In this study, immune responses elicited by an intranasal inactivated vaccine of influenza A(H5N1) virus were evaluated in healthy individuals naive for influenza A(H5N1) virus. Three doses of intranasal inactivated whole-virion H5 influenza vaccine induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Several conserved HA targets have been identified (e.g., fusion peptides in the stalk domain), and many bnAbs are proceeding to clinical trials [ 14 ]. There are also ongoing clinical trials of intranasal vaccinations with inducible neutralizing pIgAs against HA to achieve cross-protection [ 105 ]. However, it is difficult to obtain HA2 stalk-specific antibodies with natural infections or conventional vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conserved HA targets have been identified (e.g., fusion peptides in the stalk domain), and many bnAbs are proceeding to clinical trials [ 14 ]. There are also ongoing clinical trials of intranasal vaccinations with inducible neutralizing pIgAs against HA to achieve cross-protection [ 105 ]. However, it is difficult to obtain HA2 stalk-specific antibodies with natural infections or conventional vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Ichinohe et al demonstrated another effective adjuvant, a synthetic double-stranded RNA (dsRNA) polyriboinosinic polyribocytidylic acid (poly (I:C)) for intranasal vaccination [ 103 ]. Clinical studies have also suggested that secretory pIgAs, generated in response to inactivated nasally administered vaccine, play a significant role in providing protection from heterologous influenza viruses [ 104 , 105 ]. An intranasally delivered inactivated vaccine could be valuable in promoting some of the favorable immune responses elicited by LAIVs, without the risk of live virus to immunocompromised individuals.…”
Section: A Universal Intranasal Vaccination Against Influenzamentioning
confidence: 99%
“…This non-interventional study was performed using residual peripheral blood mononuclear cells collected from nine vaccinated healthy adult volunteers participating in previous interventional clinical trials for an intranasal inactivated influenza vaccine (Clinical trial registry: UMIN000008279 [ 39 ]). The study was conducted with the approval of the medical research ethics committee of the National Institute of Infectious Diseases for the use of human subjects, Tokyo, Japan (no.…”
Section: Methodsmentioning
confidence: 99%
“…920), and all participants provided written informed consent via an ethics committee-approved form. The primary outcome of the interventional clinical trial is reported separately [ 39 ]. Participants in the interventional clinical trial received three intranasal vaccinations with a monovalent WIV vaccine (45 μg HA/500 μl).…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal vaccines have been developed, and the application of intranasal H5 influenza vaccine has been shown to not only produce local secretory IgA but also to induce IgG in serum. 10 Nasal inflammatory symptoms may be more important than previously thought. The absence of nasal inflammation allows the virus to replicate effectively and rapidly in the URT.…”
Section: Mechanism Of Local Nasal Defense In Urtimentioning
confidence: 99%